THE EMPATHY FOR HUMANITY IN THE ALBUM “EVERYDAY LIFE” BY COLDPLAY - Pradana, Galih Octav; Widayanti, Maria Johana Ari (Universitas Negeri Semarang, 2024)
Coldplay is a pop and rock band born in 1996 in London, British. The objective of the study is to analyze how Coldplay expresses empathy for the current state of the world in recent years (such as wars and racism). To analyze the selected lyrics, the researcher used sign, signifier, signified by Roland Barthes combined with Charles Sanders Peirce’s index, icon symbol, and literal environment to connect these songs to the current state of society. Findings showed that the lyrics do have a humanitarian message that Coldplay wants to convey, also the delivery of empathy is different in each song. As a result, the song Orphans emphasizes empathy for war victims with the majority using index in carrying the message, Arabesque emphasizes the racism towards Arab Muslims with the majority using symbols in conveying the message, Everyday Life emphasize surviving in a difficult life which is more dominant symbols and index, Old friend emphasize the nature of friendship with the use of icons in conveying the message, and Children of Adam emphasize the equality of humans using index and icons.